2007
DOI: 10.1300/j238v01n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Communication Features on Nonprofit Organizations' Webpages for the Practice of Excellence in Public Relations

Abstract: ABSTRACT. The main aims of this study were: (1) to examine how nonprofit organizations utilize their websites as a public relations tool, especially for media relations, donor relations, volunteer relations and their interactive communication features and (2) to ascertain whether nonprofit organizations' revenues are positively correlated with the presence and prominence of their media relations, donor relations, and volunteerrelations efforts online. To accomplish this, a content analysis of 98 websites was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
4
23
0
1
Order By: Relevance
“…Several public relations researchers have concluded that public relations and the internet are inseparably linked, offering examples of how organizations use the internet to communicate with members of its community [5].…”
Section: Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Several public relations researchers have concluded that public relations and the internet are inseparably linked, offering examples of how organizations use the internet to communicate with members of its community [5].…”
Section: Literaturementioning
confidence: 99%
“…While non-profits today are acting much like for-profit businesses, they still are lagging in their use of professional public relations practices. However, the internet offers nonprofit organizations unique opportunity to reach multiple communities, including volunteers, donors and journalists [5].…”
Section: Non-profit Organizations and The Internetmentioning
confidence: 99%
See 2 more Smart Citations
“…They have to rely on the goodwill of charitable donations from individuals, corporate donors, and government agencies in order to fund their operations, to pay their employees, and to pay the overhead administrative costs (Olson, 2000;Schmid et al, 2008;Wang and Graddy, 2008;Yeon, Choi and Kiousis, 2007). Community-based nonprofits need to maintain long term relationships with their community supporters to fulfill their mission and to deliver their services.…”
Section: Recognition and Thanksgivingmentioning
confidence: 99%